Forecasting Milk Production in India: Strategic Insights for Policymakers and Farmers (Indian Journal of Extension Education, 2025)
India’s dairy sector plays a critical role in rural income, employment, and food security, contributing significantly to the nation’s GDP. This study forecasts India’s milk production for the period 2024–2033, using historical data from 1981–2023 obtained from the Department of Animal Husbandry and Dairying, Government of India. The study adopts ARIMA and Holt’s Exponential Smoothing models for the forecasting of milk production in India, both the models reflected strong fits, with ARIMA excelling in capturing temporal structures and Holt’s model focusing on linear trends. Performance metrics highlighted the high accuracy of both models, with R-squared values exceeding 0.99 and minimal error margins. The research provides actionable insights for farmers, policymakers, and other stakeholders. The results project milk production to increase steadily, reaching 315.6–321.4 million tons by 2033. The study highlights the potential of leveraging these forecasts for strategic planning, including synchronizing production with demand, improving market stability, and addressing infrastructural and environmental challenges.